Scrutinizing the relationship between language proficiency and the use of mitigated devices by Saudi learners - Alshraah, Shadi Majed; Nishat, Arjumen Sultana (Research Journal in Advanced Humanities, 2023)
This study explored the intricate relationship between language proficiency and the utilization of mitigated devices among Saudi learners. Mitigated devices refer to linguistic strategies employed to soften or moderate speech acts, such as hedging, mitigation, and indirectness, which play a crucial role in effective communication. Understanding the connection between language proficiency and mitigated devices usage among Saudi learners not only contributes to the field of linguistics but also holds significance for cross-cultural communication and education. It provided insights into the challenges faced by learners and offers guidance for fostering more culturally sensitive and effective communication strategies. To achieve this aim, 98 Saudi learners took part in this study from PSAU by replying on the Discourse Completion Test. Findings showed a significant influence of language proficiency on using internal modifications devices. Regarding the influence of social variables, advanced learners were more conscious of the effect of social power and distance in altering their strategy depending on the contextual variables. The study concluded with practical recommendations for learners, educators, and policymakers to improve language proficiency and intercultural communication competence among Saudi learners. These recommendations aimed to facilitate more effective and contextually appropriate communication in academic, professional, and social settings.